(untitled) (International Journal of Engineering and Computer Science, 2017)
-Self Compacting Concrete gets dense and compacted due to its own self-weight. An experimental investigation has been carried out to determine different characters like workability and strength of Self-Compacting Concrete (SCC). Tests involving various fiber proportions for a particular mix of SCC. Test methods used to study the properties of fresh concrete were slump test, U – tube, V – funnel and L – Box. The properties like compressive, tensile and flexural strength of SCC were also investigated. For compressive strength of studies the cube size of 100mmX100mmX100mm were used. The specimens were cured and tested for 7 and 28 days for high compressive strength. The split tensile strength was studied for the same concrete mix using cylinders size 100mmX200mm. The specimens were cured and tested for 7 and 28 days. The flexural strength was studied for the same concrete mix using beam of size 100mmX100mmX200mm. The specimens were cured and tested for 7 and 28 days.The stress-strain relationship was studied for the same concrete mix using cylinders of size 150mmX300mm. The specimens were cured and tested for 7 and 28 days. Test Results shows that the workability characteristics of SCC are within the limiting constraints of SCC. The variation of different parameters of hardened concrete with respect to various fiber contents was analysed.